Pelatihan Penggunaan Sistem Automasi Perpustakaan dengan Aplikasi SLiMS bagi Tenaga Perpustakaan pada 6 SMK Pusat Keunggulan - Riyanto, Riyanto; Adiyanto, Adiyanto; Nurasiah, Nurasiah; winanti, winanti; Himmy'azz, Istajib Kulla Kulla; Purno, Marhaendro; Kumoro, Dwi Ferdi Cahya; Kamar, Karnawi; Yulia, Yayah; Tiara, Beby; Jubaedah, Ida (IAHN Gde Pudja Mataram, 2024)
Many schools still use manual recording in borrowing and returning and there is no automation of library reports resulting in many lost books that cannot be traced. In addition, manual recording also risks not recording library materials because of the many borrowers who come. Library digitization training using the SliM application for 6 vocational schools where 4 vocational schools are in Tangerang district, 1 vocational school is in Karawang and 1 vocational school is in Malingping. The six vocational schools until the day of the training had not used the library application and were still using a conventional system by recording borrowing and returning books through a ledger although 3 schools had recorded books in Microsoft Excel but for borrowing and returning they still used manual. So it is necessary to conduct training in the use of the library application so that library materials owned by the school can be traced easily and databased and make it easier to print reports. The training was conducted at the Saba Karya Insan Pembangunan Auditorium with competent speakers, namely guided directly by librarians and Insan Pembangunan University itself has long implemented the SLiM application. Participants from 6 vocational schools were very enthusiastic in participating in this training and communication media was provided for participants if they still experienced problems using the application